Improving Students' Social Emotional Abilities Through PKN Subjects in Class X of SMAN 14 Medan - Dani, Fitri Rahma; Susilawati, Evi; Gultom, Rumesti (CV. Rayyan Dwi Bharata, 2024)
This research was written with the aim of finding out the influence of PKN learning on the development and character formation of students through improving social emotional abilities as outlined in the material on the Position of Pancasila as the Foundation of the State, View of Life and State Ideology. The background to this research is that there are learning problems caused by teachers' lack of attention to students' affective development, which hinders progress in other aspects, namely students' cognitive and psychomotor skills, the lack of students' social-emotional abilities in the classroom resulting in disharmony between students and other students. between students and teachers. These problems appear when learning is taking place, students show attitudes that are oriented towards the problem of low social emotional abilities, such as students not showing optimal self-confidence, when asked questions, students are just silent and sometimes answer with answers that are stuck to the book and lack confidence, then students do not dare to be themselves but are more fixated and less creatively active in carrying out learning activities, students are less independent in solving the problems they are given, when there are problems between fellow students the students tend to be apathetic and lack good social sense, and students lack of courage to take decisions and take responsibility. This was seen when given the order to choose a group leader, no one dared to volunteer and had to be appointed first by the teacher. The solution to these problems is provided in this research, namely by taking a social emotional learning approach to students through PKN subjects using a chain whisper game so that students can build character according to good social emotional skills. This research uses a quantitative approach with the type of research being Classroom Action Research which consists of two cycles, and each cycle has two meetings with a total of 2 cycles totaling 4 meetings, each cycle is arranged in stages namely Planning, Implementing Action, Observation and Reflection. The subjects in this research were class The results in this research were that there was a good and significant increase, where the results obtained were good with achievements passing the threshold category of 80%. Based on the data obtained above, it can be concluded that efforts to improve students' social emotional abilities have increased significantly, initially the total average at the first meeting of the first cycle was 54%, increasing to 77% and in the second cycle the initial value was 76% to 84%.. The results obtained show that the research has passed the success category limit of 80% with the final result being 84% with Good status.